2005
DOI: 10.1111/j.1524-6175.2005.04498.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Cognitive Decline: Impact on Executive Function

Abstract: (J Clin Hypertens. 2005;7:598-604)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
1
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 52 publications
(35 reference statements)
9
56
1
8
Order By: Relevance
“…Some studies have found that hypertension is a risk factor for the development of cognitive decline; on the other hand, others report that hypertension in old age is a concomitant phenomenon of already-existing cognitive impairment, rather than an independent risk factor. [23][24][25] Our findings in this very elderly population are not consistent with studies based on people aged 65 years or older. However, participants in these earlier studies were younger and had better cognitive function and lower prevalence of hypertension than the participants in this study.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Some studies have found that hypertension is a risk factor for the development of cognitive decline; on the other hand, others report that hypertension in old age is a concomitant phenomenon of already-existing cognitive impairment, rather than an independent risk factor. [23][24][25] Our findings in this very elderly population are not consistent with studies based on people aged 65 years or older. However, participants in these earlier studies were younger and had better cognitive function and lower prevalence of hypertension than the participants in this study.…”
Section: Discussioncontrasting
confidence: 57%
“…It is generally thought that hypertension and cognitive impairment are significantly and highly correlated in both younger adults and the elderly. [23][24][25] Many earlier studies have inferred causality between hypertension and cognitive impairment in old age. Some studies have found that hypertension is a risk factor for the development of cognitive decline; on the other hand, others report that hypertension in old age is a concomitant phenomenon of already-existing cognitive impairment, rather than an independent risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…PLMS has been associated with increased sympathetic activity, elevated blood pressure and incident cardiovascular diseases, 3,20 which all contribute to vascular-related cognitive impairment, as featured by impairment in executive function. [21][22][23] Moreover, dopamine deficit, as a frequently suggested cause of PLMS, 4 also plays a key role in neurodegeneration and affects particularly the prefrontal cortex area, which regulates executive function. 24,25 Previous research suggests that executive function is a better predictor of functional decline and mortality in older women 26 ; thus, the current finding on PLMS and decline in executive function might have important clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…48 Accordingly, Knecht et al 27 found that systolic BP explained up to 11% of the variance in cognitive performance in nondemented groups of individuals in midlife age, suggesting that in this population hypertension may account for onetenth of cognitive impairment and thus for an increased risk for dementia. Another study performed by Vicario et al 19 demonstrated that cognitive impairment of hypertensive patients is present in areas such as attention, memory, and executive function. 19 While evaluating middle-aged, never-treated hypertensive patients, Sierra et al 49 first described that the presence of silent cerebral white matter lesions is associated with a mild decline in basic attention.…”
Section: Discussionmentioning
confidence: 99%
“…17 The applied tests, previously used by several authors, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] can reveal such minor alterations of the cognitive function, which are not necessarily evident during everyday activity. All tests were carried out and scored by a trained psychologist.…”
Section: Neuropsychological Examinationmentioning
confidence: 99%